2017
DOI: 10.3389/fnins.2017.00613
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Neuroimaging of Music Processing Reveals Mid-Latency Changes with Level of Musical Expertise

Abstract: This original research focused on the effect of musical training intensity on cerebral and behavioral processing of complex music using high-density event-related potential (ERP) approaches. Recently we have been able to show progressive changes with training in gray and white matter, and higher order brain functioning using (f)MRI [(functional) Magnetic Resonance Imaging], as well as changes in musical and general cognitive functioning. The current study investigated the same population of non-musicians, amat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 98 publications
(195 reference statements)
0
14
0
2
Order By: Relevance
“…The present study applied electrical neuroimaging to investigate the influence of true absolute pitch on processing of complex classical music in pianists trained in the western classical repertoire. The research is a follow-up of 3 previous studies that showed progressive processing changes with musical training intensity and proficiency using the same musical stimuli (Oechslin et al, 2013 ; James et al, 2017 ; Jenni et al, 2017 ) and allows to answer the question whether true-absolute pitch offers additional advantages for music processing.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The present study applied electrical neuroimaging to investigate the influence of true absolute pitch on processing of complex classical music in pianists trained in the western classical repertoire. The research is a follow-up of 3 previous studies that showed progressive processing changes with musical training intensity and proficiency using the same musical stimuli (Oechslin et al, 2013 ; James et al, 2017 ; Jenni et al, 2017 ) and allows to answer the question whether true-absolute pitch offers additional advantages for music processing.…”
Section: Introductionmentioning
confidence: 95%
“…The musical stimuli were short expressive pieces for string quartet with 3 levels of harmonic transgression at closure that participants appraised, presented while high density EEG was recorded. We previously used these stimuli successfully to show the impact of different levels of musical training intensity on brain and behavioral responses using fMRI (Oechslin et al, 2013 ) and EEG (James et al, 2017 ), also exclusively in pianists. Both the fMRI and the EEG study results disclosed progressive changes in music processing as a function of musical training intensity and proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this multimodal characteristic, music intervention has the potential to change brain architecture that might be accompanied by cognitive changes. Although neuroanatomy (gross morphology of auditory cortex) has been shown to be extremely stable from childhood to adolescence in a longitudinal study (Seither-Preisler et al, 2014), other studies observed changes related to brain activation, as assessed by functional magnetic resonance imaging (Oechslin et al, 2013), electroencephalography (James et al, 2017), neural connectivity measured by diffusion tensor imaging (Moore et al, 2014), and cortical thickness (Hudziak et al, 2014).…”
Section: A Recent Cognitive Remediation Approach: Musical Trainingmentioning
confidence: 99%
“…Even though EEG source estimation has been applied successfully in various clinical and fundamental studies (e.g. Britz, Landis, & Michel, 2009;Corrigan et al, 2009;De Pretto, Rochat, & Spierer, 2017;Geukes et al, 2013;James, Britz, Vuilleumier, Hauert, & Michel, 2008;James et al, 2012;James, Oechslin, Michel, & De Pretto, 2017;Rihs et al, 2013;Sallard et al, 2014), such method only guarantees a 1-2 cm spatial accuracy (Martuzzi et al, 2009;Plomp, Michel, & Herzog, 2010).…”
Section: Eeg Datamentioning
confidence: 99%